O poder familiar na nova realidade jurídico-social - Reis, Clarice Moraes (2006)
The present paper, following the research line adopted by the graduate course in comparative civil law, has the purpose of analyzing the evolution of the paternal power/duty granted to the parents in relation to their children, evidencing the alteration in the family structure as an important legal event for the State. Changes and advances taken place in the family law, especially since the middle of the last century, are due to alterations in the patriarchal system, which had been always relied on the bonus pater familiae. Pater familae has been losing space at the same time women has become legal subject fully capable of rights. The historical overview of the present paper, which is the beginning of this topic, analyzes the current enforced legislation in Brazil and also in foreign countries, with the purpose of evidencing social structures that ground family organizations, and that are also influenced in the current positive law. The new Civil Code has adopted the usage of the term family power , referring so in Book IV (Family Rights), Title I (Personal Rights), Subtitle II (Blood relations), Chapter V (Family power), articles 1.630 to 1.638. It is important state that the same structure in relation to its order, sequence and content used in the previous Code has been remained. However, this structure was indeed adopted to the constitutional principles, especially in relation to the joint performance of such power by both father and mother. So, it is possible to say that the family power is a public munus that cannot be renounced nor disposed by the parents. Therefore, the purpose of this study is to analyze modifications in the family structure and justify them on the present social and legal scenario